The development of Ni based catalysts for carbon dioxide reforming of methane - Cao, Pengfei (2017)
Recently, with the rapid development of human society, meeting energy demand and controlling climate change are becoming urgent issues. Carbon dioxide (dry) reforming of methane (DRM) has been considered as a promising technology as it utilizes greenhouse gas to provide high value added liquid fuel and chemicals coupling with a Fischer-Tropsch (F-T) process. In other words, this process can both improve supply of liquid fuel and eliminate global warming issues. Since deactivation of catalysts is the major obstacle for commercialization of this approach, deep understanding of this process and development of catalysts with high activity and stability are necessary to be studied.